Assessment of planarity of the golf swing based on the functional swing plane of the clubhead and motion planes of the body points - Kwon, Y. H.; Como, C. S.; Singhal, K.; Lee, S.; Han, K. I. (Sports Biomechanics, 2012)
The purposes of this study were (1) to determine the functional swing plane (FSP) of the clubhead and the motion planes (MPs) of the shoulder/arm points and (2) to assess planarity of the golf swing based on the FSP and the MPs. The swing motions of 14 male skilled golfers (mean handicap = - 0.5 ± 2.0) using three different clubs (driver, 5-iron, and pitching wedge) were captured by an optical motion capture system (250 Hz). The FSP and MPs along with their slope/relative inclination and direction/direction of inclination were obtained using a new trajectory-plane fitting method. The slope and direction of the FSP revealed a significant club effect (p < 0.001). The relative inclination and direction of inclination of the MP showed significant point (p < 0.001) and club (p < 0.001) effects and interaction (p < 0.001). Maximum deviations of the points from the FSP revealed a significant point effect (p < 0.001) and point-club interaction (p < 0.001). It was concluded that skilled golfers exhibited well-defined and consistent FSP and MPs, and the shoulder/arm points moved on vastly different MPs and exhibited large deviations from the FSP. Skilled golfers in general exhibited semi-planar downswings with two distinct phases: a transition phase and a planar execution phase.